Math Problem Statement
Check Your Proof: Proof: Repository - hw4.5 Construct a proof for the argument: ¬(Q → R) → P, ¬P, Q ∴ R
1 ¬(Q → R) → P 2 ¬P 3 Q new linenew subproof check proofstart over
Clear & Start a new Proof Using the checker: Notation for logic operators
negation: ∼ conjunction: ^ disjunction: v conditional: -> biconditional: <-> universal quantification: Ax or (Ax) existential quantification: Ex or (Ex)
Rule names (full and abbreviated)
modus ponens ->E modus tollens MT modus tollendo ponens DS double negation DNE addition vI adjunction ^I simplification ^E bicondition <->I equivalence <->E repeat Rep conditional derivation ->I reductio ad absurdum RAA universal instantiation AE universal derivation AI existential instantiation EE existential generalization EI identity introduction =I substitution of identicals =E
Solution
To construct a proof for the argument ¬(Q → R) → P, ¬P, Q ∴ R using the formal rules of logic, we can proceed step-by-step as follows. We need to prove from the premises:
- — Premise
- — Premise
- — Premise ∴
Strategy
We will use modus tollens (MT) and reductio ad absurdum (RAA) to prove . Since we are given , the strategy is to show that assuming leads to a contradiction, thereby deriving .
Proof Steps:
Step | Statement | Justification |
---|---|---|
1 | Premise | |
2 | Premise | |
3 | Premise | |
4 | Repetition (from 2) | |
5 | Modus Tollens (1, 4) | |
6 | Double Negation Elim (5) | |
7 | Modus Ponens (6, 3) |
Explanation:
- Step 1 to 3 sets up the premises of the argument.
- Step 4 repeats the negation of for later use.
- Step 5 uses modus tollens to infer from lines 1 and 2.
- Step 6 applies double negation elimination to simplify to .
- Step 7 applies modus ponens using from line 3 and from line 6 to derive .
Thus, the conclusion follows logically from the premises.
Would you like any clarifications or further details?
Related Questions:
- What is the difference between modus tollens and modus ponens?
- How does double negation work in propositional logic?
- Can reductio ad absurdum be used in this proof as an alternative approach?
- What is the role of premises in formal proofs?
- How would the proof change if we were given instead of ?
Tip:
When working with formal proofs, it's useful to outline your strategy before diving into the detailed steps to ensure you follow a logical path.
Ask a new question for Free
By Image
Drop file here or Click Here to upload
Math Problem Analysis
Mathematical Concepts
Propositional Logic
Logical Proofs
Inference Rules
Formulas
Modus Ponens
Modus Tollens
Double Negation
Reductio ad Absurdum
Theorems
Logical Equivalences
Inference Rules in Propositional Logic
Suitable Grade Level
Undergraduate (Logic and Philosophy Courses)
Related Recommendation
Logical Proof: Constructing a Proof for P v Q, P -> ~R, R ∴ Q
Proof by Contradiction: Proving ¬s in Propositional Logic
Prove Validity of Argument: p → ∼q, r → q, r ∴ ∼p using Natural Deduction
Construct a Proof for ¬(P ↔ Q) ∴ P → ¬Q using Conditional Derivation
Proof of Validity for R→S from Logical Premises ~P∨Q, ~Q∨R, and R→S